Modelling of electric vehicle charging station and controlled by fuzzy logic controller with different modes of operation. Issue 1 (2nd January 2023) - Vijaya Kumar, S. C.; Karunanithi, K.; Raja, S. P.; Ramesh, S.; Chandrasekar, P.; Obulupathy, R.
ABSTRACT: The main objective of implementing charging stations is to ensure the good charging to the Electric Vehicles by using a solar PV array which is interconnected to the battery energy storage systems. The charging station regulates the supply voltage and frequency without the use of a mechanical speed governor. It also assures that energy gained from grid or by the DG set will have the unity power factor (UPF) when the load is nonlinear. Besides this, the Point of Common Coupling (PCC) voltage is synchronised with the grid/generator voltage in order to provide continuous charging. In order to increase the optimal efficiency of the charging stations, the charging stations will perform the active/reactive power transfer from the vehicle to grid, vehicle to house and vehicle to vehicle (V2V) power transfer. The operational experiment of the charging station is simulated and verified by using MATLAB/SIMULINK.